Akceptacja choroby w grupie kobiet leczonych chirurgicznie z powodu nowotworu piersi = Illness acceptance among women who have undergone surgical treatment for a breast neoplasm - Marta Łuczyk; Agata Pietraszek; Robert Łuczyk; Andrzej Stanisławek; Zdzisława Szadowska-Szlachetka; Marianna Charzyńska-Gula (Kazimierz Wielki University, 2015)
Łuczyk Marta, Pietraszek Agata, Łuczyk Robert, Stanisławek Andrzej, Szadowska-Szlachetka Zdzisława, Charzyńska‑Gula Marianna. Akceptacja choroby w grupie kobiet leczonych chirurgicznie z powodu nowotworu piersi = Illness acceptance among women who have undergone surgical treatment for a breast neoplasm. Journal of Education, Health and Sport. 2015;5(9):569-576. ISSN 2391-8306. DOI10.5281/zenodo.31529 http://dx.doi.org/10.5281/zenodo.31529 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A569-576 https://pbn.nauka.gov.pl/works/636504 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   Akceptacja choroby w grupie kobiet leczonych chirurgicznie z powodu nowotworu piersi Illness acceptance among women who have undergone surgical treatment for a breast neoplasm Marta Łuczyk1, Agata Pietraszek1, Robert Łuczyk2, Andrzej Stanisławek1, Zdzisława Szadowska-Szlachetka1, Marianna Charzyńska-Gula3   • 1.       Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Polska • 2.       Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Polska • 3.       Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu, Polska Streszczenie Wstęp: Istotną rolę w procesie przystosowania do choroby nowotworowej odgrywają psychologiczne zasoby takie jak zdolność dostrzeżenia i skorzystania z proponowanego wsparcia społecznego, świadomość kontroli nad sytuacjami stresującymi oraz posiadanie zainteresowań. Cel: Określenie stopnia akceptacji choroby u kobiet leczonych z powodu nowotworu piersi oraz ustalenie czy istnieje zależność między zmiennymi socjo-demograficznym a poziomem akceptacji choroby. Materiał i metody: W badaniu zastosowano metodę sondażu diagnostycznego z techniką ankiety. Do pomiaru akceptacji choroby zastosowano Skalę Akceptacji Choroby (AIS). Grupę badaną stanowiło 71 kobiet leczonych chirurgicznie z powodu nowotworu piersi. Wyniki i wnioski: W  grupie badanej aż 39,43% chorych wykazało wysoki poziom przystosowania się do choroby nowotworowej, choć średnia wartość wskaźnika akceptacji choroby, uzyskana wśród ogółu badanych pacjentek, świadczyła o ich przeciętnym stopniu akceptacji choroby. Z przeprowadzonych badań wynika, że leczone chirurgicznie z powodu nowotworu piersi, dobrze radzą sobie z pokonaniem choroby. Zmienną istotnie różnicującą poziom akceptacji choroby wśród badanych był poziom wykształcenia, najgorzej z chorobą radziły sobie kobiety z wykształceniem średnim.   Słowa kluczowe: adaptacja psychologiczna; adaptacja społeczna; nowotwory sutka. Abstract Background: In the process of dealing with neoplastic disease an important role is played by psychological resources such as the ability to recognise and use the available social support, the sense of control over stressful situations, and having hobbies and interests. Objective: To define the level of acceptance of illness among women who have undergone surgical treatment for a breast neoplasm and to verify whether there is a correlation between socio-demographic variables and the level of illness acceptance. Material and methods: In the study the diagnostic survey method was applied in combination with the questionnaire technique. The measurement was carried out with the use of the Acceptance of Illness Scale (AIS). The surveyed group consisted of 71 women who have undergone surgical treatment due to a breast neoplasm. Results and conclusions: As many as 39.43% of the surveyed patients demonstrated a high rate of adjustment to their neoplastic disease; however, the average value of the illness acceptance indicator observed among the respondents in total pointed to a medium level of illness acceptance. The research shows that women who have undergone surgical treatment for a breast neoplasm are coping well with the illness. The variable differentiating the level of illness acceptance among the surveyed was education, with the lowest coping skills presented by women with secondary education.   Key words: adaptation psychological; social adjustment; breast neoplasms.